Combining electron microscopy with single molecule DNA fiber approaches to study DNA replication dynamics - Vindigni, Alessandro (Biophys Chem, 2016)
Replication stress is a crucial driver of genomic instability. Understanding the mechanisms of replication stress response is instrumental to improve diagnosis and treatment of human disease. Electron microscopy (EM) is currently the only technique that allows to directly visualize a high number of replication intermediates and to monitor their remodeling upon stress. At the same time, DNA fiber analysis is useful to gain mechanistic insight on how genotoxic agents perturb replication fork dynamics genome-wide at single-molecule resolution. Combining these techniques has proven invaluable to achieve a comprehensive view of the mechanisms that ensure error-free processing of damaged replication forks. Here, we review how EM and single-molecule DNA fiber approaches can be used together to shed light into the mechanisms of replication stress response and discuss important cautions to be taken into account when comparing results obtained by EM and DNA fiber.